Aktueller Standard der Blutdruckmessung – Stellungnahme der Deutschen Hochdruckliga e. V. DHL® – Deutsche Gesellschaft für Hypertonie und Prävention - Eckert, Siegfried; Ott, Christian; Büchner, Nikolaus; Dechend, Ralf; Lüders, Stephan; Mengden, Thomas; Sanner, Bernd (Deutsche Medizinische Wochenschrift, 2019)
Arterial hypertension is one of the most prevalent chronic diseases, and a major risk factor for cardiovascular diseases. It is essential to perform the blood pressure measurement under standardized conditions in the office/clinical setting, otherwise inaccuracy of blood pressure values may lead to poor blood pressure control or misdiagnosis. Compliance with these standards by a trained observer is of crucial importance for a reliable and accurate blood pressure measurement in clinical practice. Regardless of the standardized assessment, it has to be kept in mind that available devices on the market may not measure blood pressure accurate enough. Therefore, a validated (e.âŠg. German Hypertension League Quality Seal) blood pressure monitor should be used. Out-of-office (home and ambulatory) blood pressure measurements provide important information beyond determining resting office/clinical BP.
CRIS-Team Scopus Importer:2019-11-05
Keywords: blood pressure measurement; standard/standardized measurement; validation/validated devices